PENANGGANAN JARINGAN IRIGASI KRUENG BARO KABUPATEN PIDIE MELALUI ANGKA KEBUTUHAN NYATA OPERAISONAL DAN PEMELIHARAAN (AKNOP) - Nofrizal Nofrizal; Azmeri Azmeri; Ella Mailianda (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
Krueng Baro Irrigation Area is one of the irrigation areas which is focused on increasing food crop productivity in Pidie District. To support the existence of the irrigation, of course, it must be supported by a well-organized irrigation system, so an effective irrigation network management system is needed through the O and M program. O and M activities require a truly real value or cost figure which is the result of the search for irrigation networks known as the real operation and maintenance demand value. The physical condition of the Krueng Baro Irrigation Network if viewed from the results of the irrigation network inventory still has many obstacles that hamper the fulfillment of rice water needs, including physical damage to buildings and irrigation channels. The evaluation of irrigation network performance is the first step in the preparation of the real operation and maintenance demand value, the rate of performance of the Krueng Baro Irrigation Area network is 68.06% (BWSSI, 2017) which falls into the less category and needs attention. This study aims to identify Irrigation Network O and M activities and the real operation and maintenance demand value Krueng Baro irrigation. The research method is in the form of observations / field observations and documentation to obtain the existing conditions of irrigation networks which subsequently identify O and M plans and preparation of the real operation and maintenance demand value. After the preparation of the real operation and maintenance demand value was obtained the output of the value of the real cost requirement in carrying out routine operations was only 0.53% (IDR 529,180,000.00), Routine Maintenance 6.52% (IDR 6,510,464,300.00), while for Periodic Maintenance is very large, namely 92.95% (IDR. 92,764,196,192.00) compared to the overall total cost (IDR. 99,803,840,492.00). In order to achieve the full O and M Plan and the real operation and maintenance demand value Krueng Baro Irrigation Network due to the limited budgetary budget so is divided into a 5-year priority program plan reference to Minister of Public Works and Housing Regulation No. 12 / PRT / M / 2015 with the first year priority carried out on the main building which greatly influences performance and function of the irrigation system such as turnover of intake doors, olak ponds and upstream weir sediment excavation and some buildings and channels that have been destroyed and not functioning on the carrier channel.